A Current-Sensor-Free Incremental Conductance Single Cell MPPT for High Performance Vehicle Solar Arrays - Wolfs, Peter; Li, Q. (IEEE, 2006)
A maximum power point tracker has been previously developed for a single high performance GaAs solar cell for hybrid and electric vehicle applications. This paper presents a new maximum power point tracking (MPPT) control algorithm which is based on the incremental conductance (IncCond) method but does not require any current sensing devices. In this new algorithm, the condition for the maximum power point (MPP) operation can be established from the solar cell voltage and the converter switching duty ratio alone. The method can also be readily applied to any load type where power increases monotonically with voltage. A solar cell model for the triple junction cell is also thoroughly discussed. This model is used in the simulation circuit and the results for the new MPPT method are provided. Finally, a solar cell simulator and a 600-mW buck converter switching at 20 kHz controlled by Texas Instrument MSP430 microprocessor are used as the test platform for the new IncCond MPPT algorithm. The experimental results show that the proposed MPPT algorithm has secured a 1.5-ms response time due to insolation changes